Va rog sa ma ajutati♥️
(x-y+3)^2=
(a-4b-3c)^2=
(2x-2y-1)^2=
Răspunsuri la întrebare
Răspuns de
2
Explicație pas cu pas:
(x-y+3)²=x²+(-y)²+3²+2*x*(-y)+2*x*3+2*(-y)*3=x²+y²+9-2xy+6x-6y
(a-4b-3c)²=a²+(-4b)²+(-3c)²+2*a*(-4b)+2*a*(-3c)+2*(-4b)*(-3c)=a²+16b²+9c²-8ab-6ac+24bc
(2x-2y-1)²=(2x)²+(-2y)²+(-1)²+2*2x*(-2y)+2*2x*(-1)+2*(-2y)*(-1)=4x²+4y²+1-8xy-4x+4y
IoanaPisi2005:
Mersi mult!
Răspuns de
1
(x-y+3)^2= x²-y²+3²-2xy-6y+6x
(a-4b-3c)^2= a²-16b²-9c²-8ab-6ac+24bc
(2x-2y-1)^2=4x²-4y²-1-8xy-4x+4y
Succes!
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă